The role of alerting in the attentional boost effect - Huang, Fajie; Lin, Guyang; Meng, Yingfang; Lin, Yuanyuan; Zheng, Siqi (Frontiers in Psychology, 2023)
Stimuli presented simultaneously with behaviorally relevant events (e.g., targets) are better memorized, an unusual effect defined as the attentional boost effect (ABE). We hypothesized that all types of behaviorally relevant events, including attentional cues, can promote the encoding process for the stimuli paired with them, and the attentional alerting network can amplify the ABE. The two experiments we conducted demonstrated that not all behaviorally relevant events, including alerting cues, benefit the processing of concurrently paired stimuli. We also found that the presence of a cue prior to a target can extend the memory advantage produced by target detection, but this advantage can only be observed within a limited range of time. Overall, our study provides the first evidence that the alerting network plays an important role in the ABE.